2022
DOI: 10.3390/biomedicines10030579
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Infiltration Correlates with Genomic Instability in Classic Hodgkin Lymphoma

Abstract: Hodgkin lymphoma (HL) is a biologically diverse group of lymphoid tumors, which accounts for 1% of all de novo neoplasms in the world’s population. It is divided into two main groups: the more common classic Hodgkin lymphoma (cHL) and the less common nodular lymphocyte-predominant Hodgkin lymphoma (NLPHL). cHL is further divided into four subtypes, which differ in morphology and the contents of tumor microenvironment. Macrophages are one of the components of tumor microenvironment known to contribute to creati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Another mechanism in which TAMs might promote tumor growth is supposed to be the induction of the genetic instability of HRS cells, probably through the release of free radicals which contribute to a mutagenic microenvironment. This was based on the observation that TP53 amplification in neoplastic cells, linked with poorer patients’ survival, was associated with increased infiltration by M2 macrophages [ 65 ].…”
Section: Overview Of Cellular Components Of Tme In Chlmentioning
confidence: 99%
“…Another mechanism in which TAMs might promote tumor growth is supposed to be the induction of the genetic instability of HRS cells, probably through the release of free radicals which contribute to a mutagenic microenvironment. This was based on the observation that TP53 amplification in neoplastic cells, linked with poorer patients’ survival, was associated with increased infiltration by M2 macrophages [ 65 ].…”
Section: Overview Of Cellular Components Of Tme In Chlmentioning
confidence: 99%
“…The literature extensively reports that overexpression of CD68+ cells in the tumor microenvironment is associated with decreased progression-free survival (PFS), overall survival (OS), and increased risk of relapse [19][20][21][22]. Different hypotheses suggest that macrophages promote genetic instability within the tumor microenvironment, thereby impacting patient survival [23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the presence of CD163 + macrophages in tumor tissue is related to poor survival in patients with classical Hodgkin lymphoma (CHL) [303]. Additionally, a lower number of TAMs in CHL samples was correlated with a higher progressionfree survival rate [304].…”
Section: Hodgkin Lymphomamentioning
confidence: 99%